Boron nitride aerogel / phase change heat conduction composite material and preparation method thereof

By introducing radial structure thermal fillers into the boron nitride aerogel, the boron nitride aerogel/phase change thermal conductivity composite is prepared by using centripetal frozen casting and chemical vapor deposition processes, the problem of low thermal conductivity of existing phase change materials is solved, and the efficient heat dissipation and thermal insulation performance is improved.

CN119842366AActive Publication Date: 2025-04-18SHANGHAI INST OF CERAMIC CHEM & TECH CHINESE ACAD OF SCI
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311340179.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-17
Publication Date
2025-04-18
Estimated Expiration
2043-10-17

AI Technical Summary

Technical Problem

The inherent low thermal conductivity and leakage problems of existing phase change materials limit their application, especially in the case of increased demand for high-performance thermally managed materials.

Method used

By introducing a radial structured thermal filler into the boron nitride aerogel, the boron nitride aerogel/phase change thermal conductivity is prepared by using a centripetal frozen casting and chemical vapor deposition process to achieve isotropic high thermal conductivity.

Benefits of technology

This method effectively improves the thermal conductivity of the composite material, achieves efficient heat dissipation, and enhances the insulation performance and stability of the material through an orderly structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119842366A_ABST
    Figure CN119842366A_ABST
Patent Text Reader

Abstract

The invention relates to a boron nitride aerogel / phase-change heat-conducting composite material and a preparation method thereof. The preparation method of the boron nitride aerogel / phase-change heat-conducting composite material comprises the following steps: (1) pouring a graphene oxide dispersion liquid into a mold, placing the mold in a low-temperature environment for freeze casting, and then performing freeze drying and heat treatment on a sample subjected to freeze casting to obtain graphene aerogel with a three-dimensional centripetal structure; (2) depositing boron nitride on the surface of graphene through an in-situ reaction by taking the graphene aerogel with the three-dimensional centripetal structure as a template and utilizing a chemical vapor deposition process to obtain graphene / boron nitride hybrid aerogel; (3) carrying out hot etching high-temperature oxidation treatment on the graphene / boron nitride hybrid aerogel to remove a graphene component so as to obtain a radial-structure boron nitride aerogel; and (4) immersing the phase-change material into the boron nitride aerogel with the radial structure under a heating condition by utilizing a vacuum-assisted impregnation method, and curing to obtain the boron nitride aerogel / phase-change heat-conducting composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of phase-change thermal conductive composite materials, and in particular relates to a boron nitride aerogel / phase-change thermal conductive composite material and a preparation method thereof. Background Art

[0002] With the continuous miniaturization, high integration and increasing power density of power equipment and electronic devices, heat dissipation has become a huge challenge for power equipment and electronic devices. Overheating caused by heat accumulation can greatly reduce the operating efficiency, reliability and life of these equipment and devices, and even cause fire risks. Nowadays, the demand for high-performance thermal management materials is increasing in many engineering fields including power transmission, energy storage, and integrated circuits. In this case, high thermal conductivity materials with excellent mechanical, electrical insulation and fire resistance have become an urgent need to solve the heat dissipation problem.

[0003] Phase change materials (PCMs), as a thermal management material, have been widely used in various fields due to their large heat storage capacity and isothermal characteristics during the phase change process. Organic PCMs, especially paraffin and polyethylene glycol (PEG), have attracted much attention due to their high latent heat, excellent cycle stability and non-toxicity. However, organic PCMs generally also have problems including low intrinsic thermal conductivity and leakage, which seriously limit their application. In order to overcome these problems, high thermal conductivity fillers (such as graphene and carbon nanotubes) are widely used to enhance the thermal conductivity of PCMs. Phase change composites based on three-dimensional thermal conductive fillers have become an effective means to improve the performance of phase change materials.

[0004] Hexagonal boron nitride (h-BN), also known as white graphite, has a similar structure to graphite and has excellent electrical insulation properties, high thermal conductivity, high thermal stability and oxidation resistance. BN usually gives PCMs higher electrical insulation and thermal conductivity. Therefore, infiltrating PCMs into BN aerogels will help prepare highly thermally conductive but electrically insulating composite PCMs, which are expected to be used in microelectronic devices. However, due to the inert surface properties of boron nitride and the weak interactions between networks, it is still difficult to construct boron nitride aerogels. Summary of the invention

[0005] In view of the above technical problems, the object of the present invention is to provide a method for preparing a boron nitride aerogel / phase change thermal conductive composite material, wherein the thermal conductive filler inside the composite material is a radial structure, which can give the composite material isotropic high thermal conductivity.

[0006] In a first aspect, the present invention provides a method for preparing a boron nitride aerogel / phase change thermal conductive composite material, the preparation method comprising the following steps: (1) pouring a graphene oxide dispersion into a mold, and then placing the mold in a low temperature environment for freeze casting, and then freeze drying and heat treating the freeze cast sample to obtain a three-dimensional centripetal graphene aerogel; (2) using the three-dimensional concentric graphene aerogel as a template, using a chemical vapor deposition process to deposit boron nitride on the graphene surface through an in-situ reaction to obtain a graphene / boron nitride hybrid aerogel; (3) subjecting the graphene / boron nitride hybrid aerogel to a thermal etching and high-temperature oxidation treatment to remove the graphene component and obtain a radial structure boron nitride aerogel; (4) Under heating conditions, the phase change material is immersed in the radial structure boron nitride aerogel by a vacuum assisted impregnation method, and the boron nitride aerogel / phase change thermal conductive composite material is obtained after curing.

[0007] Preferably, the concentration of the graphene oxide dispersion is 2 to 14 mg / mL.

[0008] Preferably, the mold is a hollow mold, preferably in the shape of a cube, a cuboid, or a cylinder; wherein the inner diameter of the cylindrical hollow mold is 6 to 20 mm, the height is 6 to 20 mm, and the mold wall thickness is 0.5 to 2 mm.

[0009] Preferably, the freeze casting is carried out in liquid nitrogen, the freeze casting temperature is controlled to be -196°C ≤ freeze casting temperature < -80°C, and the time is 3 to 10 minutes, preferably 5 minutes.

[0010] Preferably, the heat treatment process is: in an argon atmosphere, heating to 800-2000° C. at a rate of 1-10° C. / min and keeping the temperature for 1-4 hours.

[0011] Preferably, the temperature of the chemical vapor deposition process is 700-1600° C., and the deposition time is 20-80 min.

[0012] Preferably, the thermal etching high temperature oxidation treatment is carried out in air at a temperature of 600-800° C. for 20-60 min.

[0013] Preferably, the phase change material is an organic phase change material, preferably paraffin wax or polyethylene glycol; the usage ratio of the boron nitride aerogel to the phase change material is 0.02-0.1 g:0.5-1 g.

[0014] Preferably, in the vacuum-assisted impregnation method, the heating temperature is 60 to 150° C., the vacuum degree is 1 to 100 kPa, and the impregnation time is 20 min to 2 h, preferably 20 to 40 min.

[0015] In a second aspect, the present invention provides a boron nitride aerogel / phase change thermal conductive composite material obtained according to the above preparation method.

[0016] Beneficial Effects The present invention determines the microscopic orientation of the boron nitride aerogel by customizing the sacrificed graphene aerogel structure. The centripetal structural orientation of the boron nitride aerogel originates from the centripetal freeze casting. During the freeze casting process, a temperature gradient from the solution surface to the solution center is formed, that is, a centripetal temperature gradient. Ice crystals grow from the inner surface of the mold to the center under the influence of the centripetal temperature gradient. The graphene oxide sheets in the dispersion will be squeezed to the ice crystal interface by the ice crystals, replicating the outline of the ice crystals to complete the orientation process. Therefore, the boron nitride aerogel obtained after the graphene component is removed by thermal etching oxidation also has a similar structure, and this ordered orientation helps to achieve efficient heat dissipation as a thermal conductive filler. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a structural orientation diagram of the boron nitride aerogel prepared in Example 1; Figure 2 This is a microscopic morphology of the boron nitride aerogel / phase change thermal conductive composite material prepared in Example 1; Figure 3 The DSC curve of the boron nitride aerogel / phase change thermal conductive composite material prepared in Example 1; Figure 4 , 5 Microscopic morphology of the boron nitride aerogel / phase change thermal conductive composite material samples prepared in Comparative Examples 1 and 2. DETAILED DESCRIPTION

[0018] The present invention is further described by way of embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, rather than to limit the present invention.

[0019] In the present disclosure, graphene oxide is used as raw material, and graphene aerogel is obtained by centripetal freeze-drying technology and heat treatment. Based on the graphene aerogel template, a sacrificial template method is used to obtain a boron nitride aerogel with a centripetal orientation and a radial structure. Finally, a heating-assisted vacuum impregnation solid-liquid organic phase change material is used to obtain a composite thermally conductive phase change material with an ordered thermally conductive filler.

[0020] The following is an exemplary description of the preparation method of the boron nitride aerogel / phase change thermal conductive composite material provided by the present invention. The preparation method may include the following steps.

[0021] (1) Preparation of three-dimensional concentric graphene aerogel: A graphene oxide dispersion is poured into a mold, which is then placed in a low-temperature environment for freeze casting, and then the freeze-cast sample is freeze-dried and heat-treated to obtain the three-dimensional concentric graphene aerogel.

[0022] In some embodiments, the concentration of the graphene oxide dispersion may be 2 to 14 mg / mL. If the graphene concentration is too low, a three-dimensional skeleton cannot be formed; if the concentration is too high, raw materials will be wasted.

[0023] In some embodiments, the mold may be a hollow mold, preferably in the shape of a cube, a cuboid, or a cylinder. The inner diameter of the cylindrical hollow mold may be 6 to 20 mm, the height may be 6 to 20 mm, and the mold wall thickness may be 0.5 to 2 mm, so as to facilitate the subsequent acquisition of boron nitride aerogels of different sizes.

[0024] In some embodiments, the freeze casting can be performed in liquid nitrogen, controlling the temperature of -196°C ≤ freeze casting < -80°C, and the time can be 3 to 10 minutes, preferably 5 minutes. Maintaining a lower freeze casting temperature can promote a smaller aerogel pore size and a more stable structure; at the same time, complete freezing can be ensured by controlling the freezing time.

[0025] In some embodiments, the heat treatment process may be: heating to 800-2000° C. at a rate of 1-10° C. / min and keeping the temperature for 1-4 hours under an argon atmosphere. The graphene oxide may be thermally reduced to graphene by heat treatment. The higher the reduction temperature, the higher the degree of graphene reduction; the heat treatment is performed under argon to ensure that the reduced graphene will not be oxidized.

[0026] (2) Preparation of graphene / boron nitride hybrid aerogel. The three-dimensional concentric graphene aerogel is used as a template, and boron nitride is deposited on the graphene surface by in-situ reaction using a chemical vapor deposition (CVI) process to obtain the graphene / boron nitride hybrid aerogel.

[0027] In some embodiments, the temperature of the chemical vapor deposition process may be 700 to 1600° C., and the deposition time may be 20 to 80 minutes.

[0028] In some embodiments, the boron nitride ceramic precursor may be selected from boron trichloride and ammonia, trichloroborazine, and diethanolamine borate.

[0029] (3) Preparation of pure boron nitride aerogel: The graphene / boron nitride hybrid aerogel is subjected to thermal etching and high-temperature oxidation treatment to remove the graphene component, thereby obtaining a radial structure boron nitride aerogel.

[0030] In some embodiments, the thermal etching high temperature oxidation treatment may be performed in air at a temperature of 600 to 800° C. for 20 to 60 minutes.

[0031] If the temperature of the thermal etching high temperature oxidation treatment is too low, the graphene cannot be oxidized and removed; if the temperature is too high, the boron nitride will be oxidized, and the designed sample cannot be obtained. At the same time, if the time of the thermal etching high temperature oxidation treatment is too short, the graphene cannot be completely oxidized; if the oxidation treatment time is too long, the boron nitride will be slightly oxidized, which is not conducive to its performance.

[0032] (4) Preparation of boron nitride aerogel / phase change thermal conductive composite material: The boron nitride aerogel and the phase change material are placed in a drying oven together, and the phase change material is impregnated into the boron nitride aerogel by vacuum assisted impregnation under heating conditions, and the boron nitride aerogel / phase change thermal conductive composite material is obtained after curing.

[0033] In some embodiments, the phase change material can be an organic phase change material, preferably paraffin wax or polyethylene glycol; the dosage ratio of the boron nitride aerogel to the phase change material can be 0.02-0.1 g:0.5-1 g. If the dosage ratio is too low, a continuous thermal conductive skeleton cannot be formed, and the gain effect on the thermal conductivity of the composite material is not good; boron nitride has a reinforcing effect, and if the dosage is too high, a ceramic polymer composite material with a more complex and irregular morphology will be formed.

[0034] In some embodiments, in the vacuum-assisted impregnation method, the heating temperature may be 60 to 150° C., the vacuum degree may be 1 to 100 kPa, and the impregnation time may be 20 min to 2 h, preferably 20 to 40 min.

[0035] In some embodiments, the curing process may be natural cooling.

[0036] The present invention determines the microscopic orientation of the boron nitride aerogel by customizing the sacrificed graphene aerogel structure. The centripetal structural orientation of the boron nitride aerogel originates from the centripetal freeze casting. During the freeze casting process, a temperature gradient from the solution surface to the solution center is formed, that is, a centripetal temperature gradient. Ice crystals grow from the inner surface of the mold to the center under the influence of the centripetal temperature gradient. The graphene oxide sheets in the dispersion will be squeezed to the ice crystal interface by the ice crystals, replicating the outline of the ice crystals to complete the orientation process. Therefore, the boron nitride aerogel obtained after the graphene component is removed by thermal etching oxidation also has a similar structure, and this ordered orientation helps to achieve efficient heat dissipation as a thermal conductive filler.

[0037] The present invention uses centripetal freeze casting to obtain an internal structure and lamella orientation with obvious orientation. The ordered structure often has better thermal insulation performance than the disordered structure obtained by freeze drying. When used as a thermal conductive filler, it can reduce the heat loss path. In addition, the structure obtained by centripetal freeze casting gives the aerogel a negative Poisson's ratio effect. This metamaterial property makes it more stable, not only elastic, but also able to exist stably under multiple cycles of compression.

[0038] The thermal conductivity of the boron nitride aerogel / phase-change thermal conductive composite material obtained by the preparation method provided by the invention is 0.6-3 W / m·K.

[0039] The following examples are further listed to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are only examples in a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values ​​​​exemplified below.

[0040] Example 1

[0041] The preparation method of the boron nitride aerogel / phase change thermal conductive composite material provided in this embodiment 1 comprises the following steps: (1) Graphene oxide is added to deionized water and ultrasonically dispersed to obtain a graphene oxide dispersion with a concentration of 10 mg / mL; then, the graphene oxide dispersion is poured into a cylindrical hollow copper mold until it overflows, and then sealed with a copper sheet, and then the sealed mold is placed in liquid nitrogen at -196°C for freeze casting for 5 minutes, and then the completely frozen sample is vacuum freeze-dried for 48 hours; finally, it is heated to 1000°C at a rate of 5°C / min in an argon atmosphere and kept warm for 2 hours to obtain a three-dimensional centripetal graphene aerogel; (2) placing the graphene aerogel obtained in step (1) in a tubular furnace to deposit BN at a deposition temperature of 1500° C. for 50 min to obtain a graphene / boron nitride hybrid aerogel; (3) placing the graphene / boron nitride hybrid aerogel obtained in step (2) in a muffle furnace for oxidation treatment at 700° C. to obtain a boron nitride aerogel composed of pure boron nitride; (4) placing the boron nitride aerogel obtained in step (3) and paraffin in a vacuum drying oven, vacuum impregnating at 80° C. for 2 h with a vacuum degree of 20 Pa, and obtaining the boron nitride aerogel / phase change thermal conductive composite material after curing.

[0042] Tests show that the thermal conductivity of the boron nitride aerogel / phase change thermal conductive composite material prepared in Example 1 is 2.1 W / m·K.

[0043] Figure 1 This is a structural orientation diagram of the boron nitride aerogel prepared in Example 1. As can be seen from the figure, the internal layers of the boron nitride converge toward the center of the sample and are radially oriented, which is determined by the freeze casting process.

[0044] Figure 2The microscopic morphology of the boron nitride aerogel / phase change thermal conductive composite material prepared in Example 1. The left figure shows the orientation of the boron nitride in the composite material, and the right figure shows the close combination of boron nitride and paraffin. It can be seen from the figure that after vacuum-assisted impregnation, the orientation of the boron nitride layer does not change significantly, and the density is good.

[0045] Figure 3 The DSC curves of the boron nitride aerogel / phase change thermal conductive composite material prepared in Example 1. Among them, BNM-1\2\3\4 respectively represent the composite materials finally obtained when the deposition temperatures are 1600°C, 1300°C, 1100°C, and 900°C. The left figure shows the DSC curve during endothermic melting, and the right figure shows the DSC curve during exothermic solidification. It can be seen from the figure that the phase change latent heat of the phase change composite material is as low as 164.4J / g (exothermic) and 162.9J / g (endothermic).

[0046] Example 2

[0047] The preparation method of this embodiment 2 refers to that of embodiment 1, with the main difference being that the deposition time of chemical vapor deposition of BN in step (2) is 20 minutes.

[0048] Example 3

[0049] The preparation method of this embodiment 3 refers to that of embodiment 1, with the main difference being that the deposition time of chemical vapor deposition of BN in step (2) is 30 minutes.

[0050] Example 4

[0051] The preparation method of this embodiment 4 refers to that of embodiment 1, with the main difference being that the deposition time of chemical vapor deposition of BN in step (2) is 40 minutes.

[0052] Example 5

[0053] The preparation method of this Example 5 refers to that of Example 1, with the main difference being that the deposition time of chemical vapor deposition of BN in step (2) is 60 min.

[0054] Example 6

[0055] The preparation method of this embodiment 6 refers to that of embodiment 1, with the main difference being that the phase change material immersed in step (4) is polyethylene glycol.

[0056] Example 7

[0057] The preparation method of this Example 7 refers to that of Example 1, with the main difference being that the heating temperature in step (4) is 60°C.

[0058] Comparative Example 1

[0059] The preparation method of this comparative example 1 refers to that of Example 1, with the main difference being that the freeze casting temperature in step (1) is -80°C.

[0060] Comparative Example 2

[0061] The preparation method of this comparative example 2 refers to that of Example 1, with the main difference being that the freezing casting temperature in step (1) is -20°C.

[0062] Figure 4 , 5 The microscopic morphology of the boron nitride aerogel / phase change thermal conductive composite material samples prepared in Comparative Examples 1 and 2. It can be seen from the figure that the samples obtained in Comparative Examples 1 and 2 cannot form a continuous and stable skeleton, and it is difficult to obtain a phase change thermal conductive composite material with good performance.

[0063] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.

Claims

1. A method for preparing a boron nitride aerogel / phase change thermal conductive composite material, characterized in that: The preparation method comprises the following steps: (1) pouring a graphene oxide dispersion into a mold, and then placing the mold in a low temperature environment for freeze casting, and then freeze drying and heat treating the freeze cast sample to obtain a three-dimensional centripetal graphene aerogel; (2) using the three-dimensional concentric graphene aerogel as a template, using a chemical vapor deposition process to deposit boron nitride on the graphene surface through an in-situ reaction to obtain a graphene / boron nitride hybrid aerogel; (3) subjecting the graphene / boron nitride hybrid aerogel to a thermal etching and high-temperature oxidation treatment to remove the graphene component and obtain a radial structure boron nitride aerogel; (4) Under heating conditions, the phase change material is immersed in the radial structure boron nitride aerogel by a vacuum assisted impregnation method, and the boron nitride aerogel / phase change thermal conductive composite material is obtained after curing.

2. The preparation method according to claim 1, characterized in that: The concentration of the graphene oxide dispersion is 2-14 mg / mL.

3. The preparation method according to claim 1 or 2, characterized in that: The mold is a hollow mold, preferably in the shape of a cube, a cuboid, or a cylinder; wherein the inner diameter of the cylindrical hollow mold is 6 to 20 mm, the height is 6 to 20 mm, and the mold wall thickness is 0.5 to 2 mm.

4. The preparation method according to any one of claims 1 to 3, characterized in that The freeze casting is carried out in liquid nitrogen, the temperature of the freeze casting is controlled to be -196°C ≤ <-80°C, and the time is 3 to 10 minutes, preferably 5 minutes.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The heat treatment process is: in an argon atmosphere, heating to 800-2000° C. at a rate of 1-10° C. / min and keeping the temperature for 1-4 hours.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The temperature of the chemical vapor deposition process is 700-1600° C., and the deposition time is 20-80 minutes.

7. The preparation method according to any one of claims 1 to 6, characterized in that The thermal etching high temperature oxidation treatment is carried out in air at a temperature of 600-800° C. for 20-60 minutes.

8. The preparation method according to any one of claims 1 to 7, characterized in that: The phase change material is an organic phase change material, preferably paraffin or polyethylene glycol; the usage ratio of the boron nitride aerogel to the phase change material is 0.02-0.1 g:0.5-1 g.

9. The preparation method according to any one of claims 1 to 8, characterized in that: In the vacuum-assisted impregnation method, the heating temperature is 60 to 150° C., the vacuum degree is 1 to 100 kPa, and the impregnation time is 20 min to 2 h, preferably 20 to 40 min.

10. A boron nitride aerogel / phase change thermal conductive composite material obtained by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Boron nitride / graphene double-heat-conduction-base aerogel composite phase change material and preparation method thereof

    CN111662688A

  • Boron nitride nanotube aerogel / phase change heat conduction composite material and preparation method thereof

    CN112094625A

  • Construction method for preparing oriented boron nitride aerogel at low cost without freeze-drying method

    CN116375475A

  • Flexible boron nitride nanoribbon aerogel and preparation method thereof

    US20210354986A1